A COMPREHENSIVE GRAMMATICAL ANALYSIS OF THE ENGLISH LANGUAGE: STRUCTURE, FUNCTIONS, AND MODERN LINGUISTIC PARADIGMS - Tojiyeva Marxabo Akbarovna (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract   This article provides a thorough grammatical analysis of the English language, examining  its  unique  morphosyntactic  structures,  tense-aspect  systems,  and  the functional role of grammar in meaningful communication. It highlights the transition of  English  from  a  highly  inflected  Germanic  language  to  an  analytical  one, emphasizing the reliance on word order (Subject-Verb-Object) and auxiliary verbs. The  study  explores  the  complexities  of  English  syntax,  semantic  nuances  of  tense forms,  and  contemporary  challenges  in  linguistic  analysis.  This  comprehensive overview aims to enhance pedagogical approaches and deepen structural understanding for advanced learners and educators.